Eruptivity of Flaring Active Regions Based on Electric Current Neutralization and Torus Instability Analysis - Johan Muhamad; Kanya Kusano (The Astrophysical Journal Letters)
Solar flares are frequently accompanied by coronal mass ejections (CMEs) that release a significant amount of energetic plasma into interplanetary space, potentially causing geomagnetic disturbances on Earth. However, many solar flares have no association with CMEs. The relationship between solar flare and CME occurrences remains unclear. Therefore, it is valuable to distinguish between active regions (ARs) that potentially produce flares and CMEs and those that do not. It is believed that the eruptivity of a flare can be characterized by the properties of the AR from which it originates. In this study, we analyzed selected ARs that produced solar flares with and without CMEs during solar cycle 24. We carefully calculated the electric current neutralization of each AR by selecting relevant magnetic fluxes based on their connectivities using nonlinear force-free field models. Additionally, we analyzed their stabilities against the torus instability by estimating the proxies of critical heights of the ARs. We found that several noneruptive ARs, which lacked clear signatures of neutral electric currents, exhibited a more apparent relationship with high critical heights of torus instability. Furthermore, we introduced a new nondimensional parameter that incorporates current neutralization and critical height. We found that analyzing ARs based on this new parameter can better discriminate eruptive and noneruptive flare events compared to analysis that relied solely on current neutralization or torus instability. This indicates that torus instability analysis is necessary to complement electric current neutralization in characterizing the eruptivity of solar flares.